2019
DOI: 10.1186/s12933-019-0805-5
|View full text |Cite
|
Sign up to set email alerts
|

Sortilin levels are associated with peripheral arterial disease in type 2 diabetic subjects

Abstract: BackgroundSortilin is a 95-kDa protein which has recently been linked to circulating cholesterol concentration and lifetime risk of developing significant atherosclerotic disease. Sortilin is found inside different cell types and circulating in blood. Higher circulating sortilin concentration has been found in patients with coronary atherosclerosis compared to control subjects. Sortilin concentration is influenced by statin therapy.MethodsWe enrolled statin-naïve subjects with type 2 diabetes mellitus and we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 49 publications
6
43
2
2
Order By: Relevance
“…Unsurprisingly, patients with a more severe PAD, at time of enrollment, had higher Sortilin values than those with less severe disease. These results are in line with previous data [20] and support the conclusion that an association exists between Sortilin serum levels and PAD severity in T2DM patient. However, the most relevant result of our research is that in the group of patients with higher Sortilin levels at baseline, MACE incidence was more frequent, during the 12-months follow-up, compared with the lower Sortilin level group.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Unsurprisingly, patients with a more severe PAD, at time of enrollment, had higher Sortilin values than those with less severe disease. These results are in line with previous data [20] and support the conclusion that an association exists between Sortilin serum levels and PAD severity in T2DM patient. However, the most relevant result of our research is that in the group of patients with higher Sortilin levels at baseline, MACE incidence was more frequent, during the 12-months follow-up, compared with the lower Sortilin level group.…”
Section: Discussionsupporting
confidence: 93%
“…Starting from these biological supports, a detrimental role for diabetic patient has been con rmed [27]. Furthermore, Sortilin levels correlate with the presence of PAD and PAD severity in a cohort of diabetic patients [20]. The rst result of our study is that Sortilin levels at baseline correlate statistically signi cant with ABI and are higher in patients with lower ABI.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Starting from these biological supports, a detrimental role of sortilin for diabetic patient has been previously con rmed [20,31]. Furthermore, sortilin levels correlate with the presence of PAD and PAD severity in a cohort of diabetic patients [21]. Here we found that sortilin levels at baseline are higher in patients with lower ABI.…”
Section: Discussionsupporting
confidence: 61%
“…Despite similar baseline clinical characteristics-in terms of risk factor control and PAD severity-and the same endovascular approach, some patients do not encounter complications for years while other patients may have complications, even fatal, within a few months [26]. Several potential biomarkers have been proposed, some linked to patient's genetic characteristics [25,[27][28][29], many linked metabolic and in ammatory parameters [19,25,[30][31][32][33]. Among the possible candidates, the pathways linked to adipose tissue represent a promising eld of study.…”
Section: Discussionmentioning
confidence: 99%